2017
DOI: 10.1161/strokeaha.116.015956
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Mediates Hemorrhagic Transformation After Delayed Tissue Plasminogen Activator Administration in In Situ Thromboembolic Stroke

Abstract: Our results demonstrate TLR4 involvement in hemorrhagic transformation induced by delayed tPA administration, very likely by increasing matrix metalloproteinase 9 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…In line with pre-clinical reports by others [ 17 , 18 , 41 ], rt-PA caused substantial HTs in our study by 24 h post stroke, but only when given 4 h after stroke initiation. Rodent studies therefore mimic the basic clinical observation showing lower incidence of severe intracranial bleeding at onset to treatment (OTT) ≤ 90 min and a shift towards higher risk of dangerous bleeding outcome at later OTTs [ 2 ], which usually occurs within 24–36 h [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with pre-clinical reports by others [ 17 , 18 , 41 ], rt-PA caused substantial HTs in our study by 24 h post stroke, but only when given 4 h after stroke initiation. Rodent studies therefore mimic the basic clinical observation showing lower incidence of severe intracranial bleeding at onset to treatment (OTT) ≤ 90 min and a shift towards higher risk of dangerous bleeding outcome at later OTTs [ 2 ], which usually occurs within 24–36 h [ 6 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hemorrhagic transformation (HT) is a common and potentially catastrophic complication of acute ischemic stroke (AIS) in patients receiving mechanical thrombectomy (MT), 1 and it results in worse outcomes and delays the initiation of antiplatelet or anticoagulation therapy. 2 , 3 Therefore, to determine whether thrombolytic therapy is safe, it is essential to understand why HT can develop after AIS. 4 , 5 Accumulating studies indicate that old age, hypertension, thrombolytic treatment, large infarct, long reperfusion time, high baseline National Institutes of Health Stroke Scale (NIHSS) score, high systolic blood pressure, pretreatment involvement of the basal ganglia, and the extent of ischemic injury prior to administration of therapy 3 , 6 , 7 are risk factors for HT.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, delayed tPA administration (5 h post ischaemia) caused a significant increase in brain infarct volume. Many previous studies have shown that brain infarct volume was not affected by delayed tPA treatment in both a thromboembolic and filament model (Kanazawa et al, 2011;Garcia-Culebras et al, 2017). However, delayed tPA treatment has also been found to tend to aggravate brain infarct volume (Zuo et al, 2014).…”
Section: Discussionmentioning
confidence: 94%